Improved Smart Eye Tracker Communicator Using Low Resolution Webcam - Rocha, Allana L. dos S.; Silva, Leandro H. de S.; Fernandes, Bruno J. T. (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2021: Anais Estendidos da XXXIV Conference on Graphics, Patterns and ImagesDO - 10.5753/sibgrapi.est.2021.20042, 2021)
Eye tracking is a tool presented in many applications ranging from scientific research to commercial applications. One of them is assistive technologies that aim to help people with some disabilities, including communication. However, the applications usually require specific hardware components or a high computational cost. This work proposes the Smart Eye Communicator II (SEC-II), an evolution of a previously presented algorithm to detect the pupil center and the user's gaze direction in real-time, using a low-resolution webcam and a conventional computer without a need for calibration. In SEC-II, a face aligner, which gets a canonical face alignment based on translation, scale, and rotation, has been added to the system. Likewise, strategies using eye coordinates were implemented to find the dominant the algorithm eye. By implementing these new approaches, achieved 86% accuracy, even under variable and non-uniform environmental conditions. Moreover, a graphical interface was implemented connecting the SEC-II to the internet and allowing users to express their desires and watch online videos chosen by themselves.